Kampung literasi dalam potret masyarakat Desa Maredan Barat Kecamatan Tualang Kabupaten Siak - Hadriana Hadriana; Mahdum Mahdum; M. Jaya Adi Putra; Daeng Ayub Natuna (Unri Conference Series: Community Engagement, 2020)
Literacy Village is a village area that is used to create people who have broad knowledge and understanding. At the same time, it is also a program to realize the Sustainable Development Goals in 2030. An important effort made as the first step to build a Literacy Village in Maredan Barat physically is to build a Community Reading Park, as well as building positive perceptions of the community towards Literacy Village. This paper will explain the efforts made in building this Literacy Village. To get feedback and people’s perceptions about the activities done, 56 respondents were asked to give their responce to the given questionnaire. Respondents were selected by stratified random sampling. The results of the questionnaire analysis show that the community has a positive perception of the development of Literacy Village. In general, activities of Literacy Village development can be said to be successful, although there are still obstacles due to the Covid-19 pandemic.